(untitled) (Филолошки студии, 2019)
The main interests of this paper are the syntactic features of two types od adverbial hypotactic sentences in Old Church Slavonic manuscripts of the Macedonian Recension, namely: the purpose and result clauses and the causative clauses. In the purpose clauses the most characteristic conjunction is da, which is linked to the replacement of the infinitive with the da + present verb form, a linguistic feature of the South Slavic languages; apart form that, the compound jako da is used, and as innovations - radi da and zane da in the manuscript ‘Krninski damaskin’ (16th century). In the causative clauses, apart from the conjunctions jakože, poneže and zaneže, there are two conjunction compounds - poneže radi and zaneže radi, which are also used in the manuscript ‘Krninski damaskin’ and are considered as innovations in comparison to the older Old Church Slavic manuscripts of Macedonian recension (12-14th century). The second point of interest are some semantic features of the purpose clauses introduced by the verbs - moliti, prositi with the completive clauses containing the conjunction da introduced by the same verbs. As it is shown by the analysis, these two types of sentences cannot be semantically distinguished very clearly from one another, except in the purpose clauses where a conditional is used with the conjunction da. Also, there are some semantic features of the causative clauses and explicative sentences introduced by bo, oubo, nebo, which indicate a semantic closeness between the two. The causative clauses are also semantically linked to the conclusive sentences which could be one of the reasons why in these sentences the anaphorical expressions like sego radi i togo radi are frequently used.